Parameter of succession planning in family company in machine industry - Wilsen, Wilsen; Dewi, Liliana (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
Family Company is a company that hereditary from generation to next generation. The process of transfering the company from the older generation to the next generation are the key point for the regeneration. Family company that are doing the regeneration must make sure the succession process goes on well for the family company to survive in the next genereation. Succession process need to be planned accordingly and have a clear paramater on what is needed for the successor to be qualified as a good successor on the family business. This research will discuss regarding the parameter of the succession planning matters that are currently still ongoing in Company in machine industry while using the dimention of succession planning. This research will be done in qualitative method with the primary data collection using interview with family member that are currently working in the company in the successor side and from the incumbent side.